Enhancing the solar energy conversion efficiency of solution-deposited Bi2S3 thin films by annealing in sulfur vapor at elevated temperature. Issue 10 (3rd October 2017) - Zhu, Zhehao; Iyemperumal, Satish Kumar; Kushnir, Kateryna; Carl, Alexander D.; Zhou, Lite; Brodeur, Drew R.; Grimm, Ronald L.; Titova, Lyubov V.; Deskins, N. Aaron; Rao, Pratap M.
Abstract : We enhanced the solar energy conversion efficiency of solution-deposited Bi2 S3 by annealing in sulfur vapor at elevated temperature. Abstract : Bi2 S3 is a non-toxic n-type semiconductor, which has been commonly synthesized in the form of quantum dots or nanocrystalline films by solution deposition methods. Despite a favorable optical band gap of ∼1.3 eV, such films have not achieved high solar energy conversion efficiencies to date. We hypothesize that this is in part due to the presence of sulfur vacancies that, according to our density functional theory calculations, form a deep trap state in the band gap of Bi2 S3, which can act as a strong recombination channel for photoexcited charges. Here, we report a microcrystalline Bi2 S3 thin-film synthesized by annealing solution-deposited nanocrystalline Bi2 S3 in a sulfur vapor environment at 445 °C, which simultaneously increases the grain size and phase purity of Bi2 S3, fills in sulfur vacancies, and improves optical absorption. Time-resolved terahertz spectroscopy (TRTS) reveals that sulfur annealing increases the photoexcited carrier lifetime from sub-picosecond to ∼30 picoseconds, while the internal quantum efficiency of a photoelectrochemical solar cell device is increased 4-fold from ∼10% to ∼40%. In addition, TRTS reveals that the intra-grain carrier mobility in the sulfur-annealed films is ∼165 cm 2 V −1 s −1 and the long-range mobility is ∼111 cm 2 V −1 s −1 at short times, indicating that carriers are able to hop across grain boundaries. These results indicate that annealing in sulfur vapor can produce simultaneously high light absorption and charge separation efficiencies by achieving carrier diffusion length that is comparable to the light absorption depth, leading to high solar energy conversion efficiencies in Bi2 S3 .